Peran PKn dalam Menanamkan Nilai-Nilai Multikultural untuk Membentuk Warga Negara Muda Yang Toleran - Mariyani (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2018)
The diversity conflict that is currently a hot issue in Indonesia raises the question of how therole of education to be able to instill multicultural values in young citizens. This is given thatthe current multicultural values have not been optimally strived so that awareness of respectfor differences has not yet materialized. The cultivation of existing multicultural values is moreeffectively implemented through the role of subjects in the school, one of which is the Civicssubject. The mission of one of the subjects is to instill multicultural values. The importance ofgrowing multicultural values is aimed at creating tolerant citizens who are able to solveproblems peacefully and be able to respect differences. The method used in this paper istinjaun library (Library Research). The role of Civics in an effort to instill multicultural valuesinclude: 1) The cultivation of multicultural values in the preparation of lesson plans; 2) Thecultivation of multicultural values in the implementation of learning; 3) Assessment based onattitude assessment (affective); and 4) the role of Civic teachers as role models for theirstudents to instill multicultural values implemented through classroom learning.